The lipid code-dependent phosphoswitch PDK1-D6PK activates PIN-mediated auxin efflux in Arabidopsis - Tan, Shutang; Zhang, Xixi; Kong, Wei; Yang, Xiao-Li; Molnár, Gergely; Vondráková, Zuzana; Filepová, Roberta; Petrášek, Jan; Friml, Jiří; Xue, Hong-Wei (Nature plants, 2020)
Directional intercellular transport of the phytohormone auxin mediated by PIN-FORMED (PIN) efflux carriers has essential roles in both coordinating patterning processes and integrating multiple external cues by rapidly redirecting auxin fluxes. PIN activity is therefore regulated by multiple internal and external cues, for which the underlying molecular mechanisms are not fully elucidated. Here, we demonstrate that 3'-PHOSPHOINOSITIDE-DEPENDENT PROTEIN KINASE1 (PDK1), which is conserved in plants and mammals, functions as a molecular hub that perceives upstream lipid signalling and modulates downstream substrate activity through phosphorylation. Using genetic analysis, we show that the loss-of-function Arabidopsis pdk1.1 pdk1.2 mutant exhibits a plethora of abnormalities in organogenesis and growth due to defective polar auxin transport. Further cellular and biochemical analyses reveal that PDK1 phosphorylates D6 protein kinase, a well-known upstream activator of PIN proteins. We uncover a lipid-dependent phosphorylation cascade that connects membrane-composition-based cellular signalling with plant growth and patterning by regulating morphogenetic auxin fluxes.
Keywords: 3-Phosphoinositide-Dependent Protein Kinases; proteiny huseníčku; membránové transportní proteiny; Arabidopsis; Indoleacetic Acids; fosfolipidy; proteinkinasy PDK; regulátory růstu rostlin; buněčná membrána; Arabidopsis Proteins; Membrane Transport Proteins; kyseliny indoloctové; Phospholipids; Plant Growth Regulators; Cell Membrane